2023
DOI: 10.1021/acs.inorgchem.2c03752
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Structure of Samarium Diiodide in a Tetrahydrofuran–Water Mixture

Abstract: Chemoselective reductive conversion of organic and inorganic compounds has been developed by the combination of samarium(II) diiodide (SmI2) and water. Despite the extensive previous studies to elucidate the role of water in the reactivity of SmI2, the direct structural data of the reactive Sm2+–water complexes, SmI2(H2O) n , in an organic solvent–water mixture have not been reported experimentally so far. Herein, we performed the structure analysis of the Sm2+–water complex in tetrahydrofuran (THF) in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
1
2
0
Order By: Relevance
“…1%) longer than those of the X-ray structure (see Section S2.1 in the Supporting Information). A similar pattern of slight overestimation of Sm–ligand distances is seen when comparing the optimized Sm–O and Sm–I distances of SmI 2 (THF) 4 H 2 O with those obtained from in situ X-ray absorption spectroscopy on a 1:1 mixture of SmI 2 and water in THF . More generally, the PW6B95 functional, with or without empirical dispersion corrections, has been found to perform well across a broad range of transition-metal chemistry, including the prediction of spin-state stability, as well as main-group chemistry. , …”
Section: Methodssupporting
confidence: 54%
See 1 more Smart Citation
“…1%) longer than those of the X-ray structure (see Section S2.1 in the Supporting Information). A similar pattern of slight overestimation of Sm–ligand distances is seen when comparing the optimized Sm–O and Sm–I distances of SmI 2 (THF) 4 H 2 O with those obtained from in situ X-ray absorption spectroscopy on a 1:1 mixture of SmI 2 and water in THF . More generally, the PW6B95 functional, with or without empirical dispersion corrections, has been found to perform well across a broad range of transition-metal chemistry, including the prediction of spin-state stability, as well as main-group chemistry. , …”
Section: Methodssupporting
confidence: 54%
“…A similar pattern of slight overestimation of Sm−ligand distances is seen when comparing the optimized Sm−O and Sm−I distances of SmI 2 (THF) 4 H 2 O with those obtained from in situ X-ray absorption spectroscopy on a 1:1 mixture of SmI 2 and water in THF. 16 More generally, the PW6B95 functional, with or without empirical dispersion corrections, has been found to perform well across a broad range of transition-metal chemistry, 17 including the prediction of spin-state stability, 18 as well as main-group chemistry. 19,20 The input geometries of SmI 2 (THF) 5 /SmI 2 (THF) 5 + were taken from ref 8, in which the structure of SmI 2 in THF has been explored computationally.…”
Section: ■ Computational Methodsmentioning
confidence: 99%
“…Our group has been exploring a samarium diiodide (SmI 2 ) mediated elimination/isomerization process for asymmetric carbon atom synthesis. We have found that upon treatment with SmI 2 and water ([Sm­(H 2 O) n ]­I 2 ), , substrates of type A are transformed into alkene products B in high yield and in some cases high diastereoselectivity (up to 90:10; Scheme ). The reaction is thought to proceed through a chelated organosamarium intermediate ( Sm–I ), formed upon the reduction and loss of the benzoyl ester (OBz).…”
mentioning
confidence: 99%